Examining School Security Measures as Moderators of the Association Between Homophobic Victimization and School Avoidance. (2nd April 2016) - Fisher, Benjamin W.; Tanner-Smith, Emily E.
Abstract : Homophobic victimization is a pervasive problem in U.S. schools that leads to negative outcomes for students. Those who experience homophobic victimization are at greater risk for avoiding particular spaces in school because they feel unsafe or afraid. Visible school security measures (e.g., security guards, metal detectors, and cameras) offer spatial guardianship that may reduce students' place-specific avoidance behaviors. To test this moderating effect of school security, we analyzed data from six panels of the School Crime Supplement to the National Crime Victimization Survey (N = 41, 229). Logistic regression models were used to examine the moderating effect of three types of school security measures on the association between homophobic victimization and avoidance of six specific locations in school and overall fear of victimization at school. Results suggest that visible security measures did not meaningfully moderate the association between homophobic victimization and school avoidance.